1984
DOI: 10.1007/bf01655086
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of ten cases of parathyroid carcinoma: Importance of an initial en bloc tumor resection

Abstract: This report examines the charcteristics of 10 patients surgically treated for unequivocal parathyroid carcinoma. Seven cases were from our series of 165 patients with primary hyperparathyroidism. Routine determination of serum calcium level by an automated analyzer occasionally led to early tumor detection. A spectrum of clinical and pathological variation was evident in our series. One of 3 patients with simple tumor resection and 1 of 4 patients with wide local excision in the initial operation showed local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
69
0
4

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 7 publications
1
69
0
4
Order By: Relevance
“…Segundo Fujimoto e col., a excisão cirúrgica pode ser curativa quando a natureza maligna do tumor é reconhecida de imediato na primeira cirurgia, proporcionando uma ressecção adequada do tumor, podendo incluir a remoção do istmo da tiróide e lobo ipsilateral, excisão de qualquer músculo esquelético intimamente envolvido pelo tumor e ressecção do nervo laríngeo recorrente se comprometido (41). É descrita uma incidência de 32% de metástase em linfonodos cervicais, sugerindo-se assim a retirada de todos os linfonodos do leito traqueoesofágico e uma dissecção cirúrgica cervical radical (41). Na nossa casuística, houve 2 recidivas com óbito, demonstrando a agressividade da doença.…”
Section: Discussionunclassified
“…Segundo Fujimoto e col., a excisão cirúrgica pode ser curativa quando a natureza maligna do tumor é reconhecida de imediato na primeira cirurgia, proporcionando uma ressecção adequada do tumor, podendo incluir a remoção do istmo da tiróide e lobo ipsilateral, excisão de qualquer músculo esquelético intimamente envolvido pelo tumor e ressecção do nervo laríngeo recorrente se comprometido (41). É descrita uma incidência de 32% de metástase em linfonodos cervicais, sugerindo-se assim a retirada de todos os linfonodos do leito traqueoesofágico e uma dissecção cirúrgica cervical radical (41). Na nossa casuística, houve 2 recidivas com óbito, demonstrando a agressividade da doença.…”
Section: Discussionunclassified
“…3 Since that time, several reviewers have confirmed that initial en bloc surgical excision provides the only chance for cure. 1,4 Several studies have reported that neither adjuvant chemotherapy nor radiation therapy (RT) plays a role in improving outcome. 2,[5][6][7] Postoperative progression of parathyroid carcinoma is often fatal.…”
mentioning
confidence: 99%
“…Unfortunately, intraoperative frozen-section is ineffective in order to confirm diagnosis of cancer [9]. If carcinoma is suspected on laboratory investigation, and the findings intraoperatively reveal the existence of carcinoma, en bloc resection should be conducted at initial surgery because of the confirmation of PC following pathological evaluation [12,19]. Patients for whom no en bloc resection was performed but diagnosed with PC via pathological examination should be re-assessed for surgery due to thyroidectomy, isthmectomy, paratracheal and central lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%